Study on the evolution mechanism of concrete properties under the coupled effects of freeze-thaw cycle, chloride salt and fatigue loading - Yang, Siqi; Zhang, Jiawen; Zhang, Weijie; Dong, Qi; Xiang, Li; Sun, Guoxing; Jiang, Jinyang (Frontiers in Physics, 2025)
The long-term durability performance of ballastless track systems exhibits significant dependence on their in-service environmental conditions. In addition to cyclic fatigue loading from train operations, critical durability challenges arise from the coupled effects of freeze-thaw cycling and chloride ion penetration, particularly in coastal regions or cold climate zones. Conventional experimental studies predominantly focus on single or dual-factor acceleration tests and confined to macroscopic performance characterization. In this study, the coupling effect of freeze-thaw, chloride salt and loading on the microstructure evolution was systematically and quantitively investigated, with the role of each kind of environmental action analyzed, experimentally and quantitively evaluating the significantly greater damage by freeze-thaw and chloride salt erosion to concrete than that of fatigue load.